The Reflection of Nasimi'S Concepts in The Works of Atoi - Amonova, Zilola (FILOLOGIYA UFQLARI JURNALI, 2024)
hi rhe mysticism literature o f the East, various controversial it leas about Nasi mi ami his ideas are widespread The stories about imamiddin Nasim i и re widely given in the works o f Atoi, Lutft, Gadoi, Sakkoki. Latifi. la addition, many poets were inspired by the ideas of Imamiddin Nasim I and quoted his name and ideas in their poems, in particular this situation is reflected in the work o f Atoi. The article analyzes Atoi s wta/om about Ima middin Nasi mi and his ideas o f the mysticism sect, h is worth mentioning (hat the Sufi poet also mentioned the name o f imamiddin Nasim i in his works related to the Qur'an and expressed his views. In covering this issue, attention u paid to Nasi mi 's contribution to the development o f the genre o f mysticism, his unique style and artistic skills, unlike other poets. The study used analytical and comparative methods.